Displacement : global conversations on refuge - Pasquetti, Silvia; Sanyal, Romola, 1979- (Manchester University Press, 2020)
As an unprecedented number of people are displaced around the world, scholars continue to strive to make sense of what appear to be a series of constantly unfolding 'crises.' Drawing on research in a range of regions - from Latin America, to Europe, sub-Saharan Africa, North America, post-Soviet regions, and South and South-East Asia - Displacement offers an interdisciplinary and transnational approach to thinking about structures, spaces, and lived experiences of displacement. The contributors engage in a historical, transnational, interdisciplinary dialogue to offer different ways of theorizing about refugees, internally displaced persons, stateless people and others that have been forcibly displaced. Representing a collective effort by sociologists, geographers, anthropologists, political scientists, historians and migration studies scholars, this volume develops new cross-regional conversations and theoretically innovative vocabularies in the work on forced displacement. It also draws forced displacement together with other contemporary issues across different disciplines such as urbanisation, race, and imperialism.